WAYS TO IMPROVE MOTIONAL ACTIVITY OF STUDENTS IN THE CONDITIONS OF DISTANCE LEARNING - Hordiienko, O. I.; Movchan, V. P. (Rehabilitation and Recreation, 2022)
The modern educational process in the Free Economic Zone often leads to the deterioration of students’ health. The transition of students to distance learning technology, according to experts, can cause adverse changes in functional status due to low motor component and significant mental stress. This situation requires improving the rational organization of motor activity of students in distance learning. Purpose: to reveal specially organized forms of motor activity of students in the conditions of distance learning and to investigate features of influence of a motor mode on indicators of a physical condition of subjects. Research methods: analysis of scientific and methodological literature, pedagogical, sociological observation, method of functional tests, method of indexes, methods of mathematical statistics. The research was conducted at the Hryhoriy Skovoroda University of Pereyaslav. The study involved 136 students – 68 boys and 68 girls. Results. Analysis of the results of the study shows that the transition to distance learning has led to a decrease in physical activity of students, increasing the length of their stay at the computer, which resulted in a deterioration in their well-being. To improve the motor mode of students, we developed a specially organized weekly model of physical activity, which included: a list of forms of physical education, the number of hours per week, their estimated energy value and determine the content of each form of classes, hours. The model aims to achieve adequate standards of physical activity and energy consumption. The introduction of the proposed model in the lifestyle of students was to improve their physical condition and well-being. Novelty: the paper substantiates the feasibility of physical activity in order to develop and improve motor activity of students, as well as indicative sets of exercises that can be used in the educational practice of physical education. Practical significance: the rational organization of physical activity on the basis of the integrated use of various forms of classes will improve the physical condition and well-being of students. Conclusions. The results of the study indicate the feasibility of implementing the developed model of motor activity specially organized in the mode of students in terms of distance learning.